Otters love to play - London, Jonathan 1947- (Candlewick Press, 2016)
"Ka-splash! "Head to the river, where a frolicsome bunch of otters plays all year round in a nonfiction story sprinkled with facts and loaded with fun....
Includes index
Keywords: Fiction / fast / (OCoLC)fst01423787; Juvenile works / fast / (OCoLC)fst01411637; North American river otter / fast / (OCoLC)fst01430913; Otters / fast / (OCoLC)fst01049042; Picture books for children / fast / (OCoLC)fst01063717; Play / fast / (OCoLC)fst01066938; Seasons / fast / (OCoLC)fst01110447; North American river otter -- Juvenile literature; Otters -- Juvenile literature; Play -- Juvenile fiction; Seasons -- Juvenile fiction; Picture books for children; North American river otter; Otters; Play; Seasons; Jahreslauf; Otter; Bilderbuch; Sachbilderbuch